The analysis of middle school students’ anxieties-apprehensions about mathematics in terms of different variables - (:unkn) unknown (Sakarya University, 2016)
The purpose of this study is to analyze mathematics anxiety which appears in situations requiring to deal mathematics like solving mathematical problems and dealing with numbers and also which is defined as an irrational fear, in terms of different variables. The study was designed according to scanning model for this purpose. The study group is composed of 466 students who are studying in a public school within İzmit province of Kocaeli. As a data collection tools; ‘Demographics Information Form (DIF)’ and ‘Mathematics Anxiety-Apprehension Survey (MAAS)’ were used. In research results; it is found that mathematics anxiety of the students shows significant differences according to situations such as whether they are good at Mathematics or not, whether or not they have a separate room for studying, the length of time they allocated to study mathematics, whether or not they understand mathematics, whether they love mathematical games or not and whether they hope to have a job related with mathematics in the future or not. In addition to this, it is determined that students’ mathematics anxieties did not differ significantly according to the fact that whether students are receiving extra help while doing their mathematics homework or not. © The Turkish Online Journal of Educational Technology.
Keywords: Anxiety; Apprehension; Different variables; Mathematics